Synthetic lethality on drug discovery: an update on cancer therapy. (2nd July 2020) - Yar, M. Shahar; Haider, Kashif; Gohel, Vivek; Siddiqui, Nasir Ali; Kamal, Ahmed
ABSTRACT: Introduction: A novel anticancer therapy is the need of the hour due to growing incidences of resistance to first line cancer chemotherapy. Synthetic lethality (SL) is one of the new age treatment methods being explored for combating the resistance to anticancer agents. In this method, cell mutations are exploited for the development of new therapeutic agents, where, if there is loss of function of one gene, the cell mutations can still be fixed by alternative machinery but if two genes involved in DNA repair undergo loss of function, it causes lethality to the cell. Areas covered: The authors condense findings of SL-based novel anticancer regimen. The review emphasizes some of the SL based clinical and preclinical studies of novel targets and therapy. Expert opinion: SL conceptualizes a resolution against treatment resistance to anticancer regimen by recognition of therapeutic vulnerabilities in particular cancer cells. A multitude of clinical trials associated with SL and DNA repair are being conducted that will be useful in obtaining a clearer picture pertaining to the use of cancer biomarkers and effectiveness of drugs acting via target-based molecular changes. Furthermore, new anticancer regimen focused on personalized medicines will emerge basing their development upon SL.